2019 IEEE 5th International Conference on Collaboration and Internet Computing (CIC) 2019
DOI: 10.1109/cic48465.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Provider Networks in the Neonatal Intensive Care Unit Associate with Length of Stay

Abstract: We strive to understand care coordination structures of multidisciplinary teams and to evaluate their effect on post-surgical length of stay (PSLOS) in the Neonatal Intensive Care Unit (NICU). Electronic health record (EHR) data were extracted for 18 neonates, who underwent gastrostomy tube placement surgery at the Vanderbilt University Medical Center NICU. Based on providers' interactions with the EHR (e.g. viewing, documenting, ordering), provider-provider relations were learned and used to build patient-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…Research has shown that a 1-day window is enough to capture the meaningful, collaborative relationships among HCWs [20][21][22][23]. Therefore, we assumed that there was a connection between two HCWs who interacted with the same patient's EHR on the same day.…”
Section: Modeling Hcw Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that a 1-day window is enough to capture the meaningful, collaborative relationships among HCWs [20][21][22][23]. Therefore, we assumed that there was a connection between two HCWs who interacted with the same patient's EHR on the same day.…”
Section: Modeling Hcw Networkmentioning
confidence: 99%
“…As EHR adoption has spread, the proportion of HCW activities (eg, the review of notes, requests for x-rays, and the management of medication) that involve EHRs has increased [18,19]. Thus, interactions with EHRs provide an opportunity for studying the collaborations among HCWs [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…We extracted EHR data of 15 NICU gastrostomy patients from the day prior to the patient's surgery day until postoperative day 30. The study aims to validate the associations between health-care worker networks and post-surgical length of stay (PLOS) [36]. For each patient ICU stay, we built a directed network to show how information was received and disseminated among health-care workers in the NICU.…”
Section: Length Of Stay and Nicu Team Structuresmentioning
confidence: 99%
“…Highly granular and widely available EHR audit logs document HCW activities occurring within EHRs [20][21][22][23] and can be used to model latent collaboration among HCWs and the respective interactions between HCWs and EHR systems [13,16,[24][25][26][27][28][29]. Typically, each event documented in an audit log includes a timestamp, the type of action involved, the involved HCW and patient IDs, and further metadata, such as HCW specialties, patient demographics, and health conditions [13,16,[20][21][22][23][24][25][26][27][28][29]. EHR audit logs have been widely used to measure health care organizational structures [20,25], clinical workflows [20,30,31], trauma care team structures [13,20,26], and intensive care unit care structures [16,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, each event documented in an audit log includes a timestamp, the type of action involved, the involved HCW and patient IDs, and further metadata, such as HCW specialties, patient demographics, and health conditions [13,16,[20][21][22][23][24][25][26][27][28][29]. EHR audit logs have been widely used to measure health care organizational structures [20,25], clinical workflows [20,30,31], trauma care team structures [13,20,26], and intensive care unit care structures [16,[27][28][29]. Existing studies have investigated audit log data at a coarse-grained level to build connections between HCWs [13,16,[20][21][22][23][24][25][26][27][28][29][30][31], and thus, much of the contextual information (eg, HCW-EHR system interactions) is lost.…”
Section: Introductionmentioning
confidence: 99%